Shantala as non-pharmacological therapy for pain relief in hospitalized children (Research, Society and Development, 2020)
Objective: To verify the effect of shantala on pain management in hospitalized children. Methods: This is an experimental non-controlled study with a quantitative approach, conducted from September 2018 to May 2019, in the pediatric sector of a university hospital, with children from zero to six months of age. Data analysis was performed with the aid of the Software Statistical Package for the Social Science version 21.0. Absolute and relative frequencies, epidemiological and clinical characteristics and variations of vital parameters before and after the implementation of the technique were analyzed. The Wilcoxon test was used for the numerical paired variables, considering a 95% confidence interval. Results: The sample consisted of 50 pediatric patients, with a mean age of 1.54±1.84 months. It was observed that there was a significant relationship between shantala and increased oxygen saturation and temperature, and decreased respiratory rate. The nominal frequencies of pain categories expressed before and after shantala were reduced, showed a reduction in the category "mild pain" and a considerable increase in the "pain-without-pain" category. Conclusions: The evidence indicated that the application of shantala therapeutic massage is a non-pharmacological means of great relevance for pain relief and adequacy of vital parameters of hospitalized children.